Pengaruh Pengeluaran Konsumsi Rumah Tangga Terhadap Tingkat Penggunaan E-money di Indonesia - Pratama, Abima Yunka; Cahyono, Hendry (Universitas Negeri Surabaya, 2023)
Payment technology has experienced quite rapid development in the world of transactions and consumption. The innovative payment technology allows users to make payments via their mobile phones without physically carrying payment instruments by entering the information required for transaction authentication in one channel. This research aims to examine and analyze the effect of household consumption expenditure on the level of e-money use in Indonesia. This study uses quantitative research as the method with explanatory research which explains the influence of the independent variable on the dependent variable. The results of this study indicate that there is a positive relationship between household consumption expenditure on the level of use of e-money in Indonesia